Impact of crystalline defects in 4H-SiC epitaxial layers on the electrical characteristics and blocking capability of SiC power devices - Kodolitsch, Elisabeth; Sodan, Vice; Krieger, Michael; Weber, Heiko B.; Tsavdaris, Nikolaos (Materials Research Express, 2022)
In this study, we report the impact of structural 4H-SiC epitaxial defects on the electrical characteristics and blocking capabilities of SiC power devices. The detection and classification of the various crystal defects existing in 4H-SiC epitaxial layers and substrates was carried out with a commercial inspection tool using an optical microscope with a photoluminescence channel (PL). After the fabrication of dedicated test structures, devices that contain a single crystal defect were selected and electrically tested in reverse bias mode. Photon emission microscopy was performed to enable the localization of the leakage current spots within the devices. Thus, a direct correlation of the various crystal defects with the reduced blocking capability mechanism was made. This evaluation helps to set directions and build a strategy towards the reduction of critical defects in order to improve the performance of SiC devices for high power application

Impact of Epitaxial Defects on Device Behavior and their Correlation to the Reverse Characteristics of SiC Devices - Kodolitsch, Elisabeth; Sodan, Vice; Krieger, Michael; Tsavdaris, Nikolaos (Materials Science Forum, 2022)
In this work we report on the impact of various crystalline defects present in 4H-SiC epitaxial layers on the electrical blocking characteristics of SiC power devices. Dedicated test structures were fabricated and electrically characterized in reverse bias mode. SiC substrate and epitaxial crystal defects, as well defects due to front-end processing were detected and classified using commercial inspection tools. Devices with a single defect-type were studied which leads to a direct correlation of the leakage current spot position within the device and the obtained blocking characteristics. This gives a better understanding of each crystal defect impact on device ́s performance which leads to an improvement in the reliability and cost reduction of SiC power devices.<br

Structural investigation of triangular defects in 4H-SiC epitaxial layers as nucleation source for bar shaped stacking faults (BSSFs) - Kodolitsch, Elisabeth; Kabakow, A.; Sodan; Krieger, Michael; Weber, Heiko B.; Tsavdaris, N. (Journal of Physics D: Applied Physics, 2023)
The formation of recombination-induced bar shaped stacking faults (BSSFs) during forward voltage operation of SiC devices, can lead to increased voltage drop and enhanced device degradation. In this study, a triangular epitaxial defect is identified as a nucleation source for the growth of BSSF in forward-biased 4H-SiC p-n diode test structures. We performed low and high voltage current emission microscopy measurements in order to detect the position of BSSFs in the active area of the device and in-depth structural analysis to locate their nucleation source. It was found that basal plane dislocations that converted into threading screw dislocations, close to the surface of the epitaxial layer and included in the triangular defect, act as nucleation source for the BSSFs. Those BSSFs expand from the top towards the bottom of the epitaxial layer, which is a newly reported expansion mechanism compared to the already reported BSSFs growing from the substrate/epitaxial layer interface towards the epitaxial layer surface.
CRIS-Team Scopus Importer:2023-05-26
Keywords: 4H-SiC; bipolar degradation; single Shockley stacking faults; triangular defects

Structural investigation of triangular defects in 4H-SiC epitaxial layers as nucleation source for bar shaped stacking faults (BSSFs) - Kodolitsch, Elisabeth; Kabakow, A.; Sodan, Vice; Krieger, Michael; Weber, Heiko B.; Tsavdaris, Nikolaos (Journal of Physics D-Applied Physics, 2023)
The formation of recombination-induced bar shaped stacking faults (BSSFs) during forward voltage operation of SiC devices, can lead to increased voltage drop and enhanced device degradation. In this study, a triangular epitaxial defect is identified as a nucleation source for the growth of BSSF in forward-biased 4H-SiC p-n diode test structures. We performed low and high voltage current emission microscopy measurements in order to detect the position of BSSFs in the active area of the device and in-depth structural analysis to locate their nucleation source. It was found that basal plane dislocations that converted into threading screw dislocations, close to the surface of the epitaxial layer and included in the triangular defect, act as nucleation source for the BSSFs. Those BSSFs expand from the top towards the bottom of the epitaxial layer, which is a newly reported expansion mechanism compared to the already reported BSSFs growing from the substrate/epitaxial layer interface towards the epitaxial layer surface.<br